SOME MANAGEMENT CHALLENGES FOR FOOD COMPANIES IN THE REPUBLIC OF SERBIA AND BOSNIA AND HERZEGOVINA - Đoković, Fillip; Pejanović, Radovan; Đorđević Boljanović, Jelena; Dobrijević, Gordana; Mojsilović, Miloš (Economics of Agriculture, 2018)
This paper aims to explore controlling, one of the key management functions, and autonomy at work, a determinant of employee control. Another purpose of this research is to examine the differences in autonomy or, more precisely, to find out to what degree autonomy among nonmanagers may affect creativity, innovation and business performance of an organization. The research was performed in food companies in the Republic of Serbia and Bosnia and Herzegovina. The data collected via a questionnaire were analysed by the SPSS statistical software. Five-level Likert scale was used to rate the responses. The main findings show that employees in food companies in Serbia perceive a higher level of autonomy than their counterparts in Bosnia and Herzegovina, and that the level of autonomy varies among different departments, the highest being in marketing and sales.